2013
DOI: 10.1186/2051-5960-1-36
|View full text |Cite
|
Sign up to set email alerts
|

Expression of TMEM106B, the frontotemporal lobar degeneration-associated protein, in normal and diseased human brain

Abstract: BackgroundFrontotemporal lobar degeneration (FTLD) is the second most common cause of dementia in individuals under 65 years old and manifests as alterations in behavior, personality, or language secondary to degeneration of the frontal and/or temporal lobes. FTLD-TDP, the largest neuropathological subset of FTLD, is characterized by hyperphosphorylated, ubiquitinated TAR DNA-binding protein 43 (TDP-43) inclusions. Mutations in progranulin (GRN), a neuroprotective growth factor, are one of the most common Mend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…We first sought to determine the localization and functional implication of TMEM106B expression by establishing both murine (344SQ, 393P, and LLC-JSP) and human (H157 and HCC827) cell lines with inducible expression of full-length, green fluorescent protein (GFP)-tagged TMEM106B . We observed that irrespective of the cell type, within 24–48 h of TMEM106B induction there was robust expression of the GFP-tagged TMEM106B (Supplementary Figure 2A ), which was associated with formation of enlarged membrane bound vesicles in comparison to GFP-expressing control cells, which has also been reported in other cell types upon ectopic expression of TMEM106B 14 , 37 39 , (Fig. 3 a1–2, b1–2 and c1– 2 and Supplementary Figures 2 B1-2, 2D ).…”
Section: Resultssupporting
confidence: 75%
“…We first sought to determine the localization and functional implication of TMEM106B expression by establishing both murine (344SQ, 393P, and LLC-JSP) and human (H157 and HCC827) cell lines with inducible expression of full-length, green fluorescent protein (GFP)-tagged TMEM106B . We observed that irrespective of the cell type, within 24–48 h of TMEM106B induction there was robust expression of the GFP-tagged TMEM106B (Supplementary Figure 2A ), which was associated with formation of enlarged membrane bound vesicles in comparison to GFP-expressing control cells, which has also been reported in other cell types upon ectopic expression of TMEM106B 14 , 37 39 , (Fig. 3 a1–2, b1–2 and c1– 2 and Supplementary Figures 2 B1-2, 2D ).…”
Section: Resultssupporting
confidence: 75%
“…Since accumulation of lysosomes in the soma and proximal dendrites is a common finding in brain tissue of FTLD patients particularly with GRN mutations (Chen‐Plotkin et al , ; Busch et al , ), we analyzed the localization of TMEM106B in rat primary hippocampal neurons. Consistent with previous reports (Chen‐Plotkin et al , ; Lang et al , ), endogenous TMEM106B colocalized with LAMP1‐positive late‐endosomal/lysosomal vesicles in the cell body and in dendrites (Fig A).…”
Section: Resultsmentioning
confidence: 99%
“…Microglial dystrophy is clearly altered in both sporadic and genetic FTLD, so lipid handling, lysosomal function or other pathways contributing to senescence could be valuable therapeutic targets. However, microglial function is complex and is likely influenced not only by mutations in FTD-associated genes known to affect microglial or lysosomal function (such as GRN , C9orf72 , MAPT , TBK1 , SQSTM1 , VCP or CHMP2B ), but also by polygenic variants in immune system genes linked to FTD, such as HLA loci [ 81 , 82 ] or TREM2 [ 83 , 84 ] and in lysosomal genes linked to variability in FTLD- GRN and FTLD- C9orf72 such as TMEM106B , SORT1 and PSAP [ 79 , 85 88 ]. Variants in immune pathway or lysosomal genes linked to variability in sporadic disease, such as FTLD-TDP ( HLA-DQA2 , DHX58 , TRIM21 , IRF7 ) [ 89 ], and multiple other external and environmental factors, may play a role in determining the fate of microglia in an aging individual that develops sporadic disease.…”
Section: Discussionmentioning
confidence: 99%